A SEGMENT OF INCA ROAD IN TUTIWAYQO, TAMBILLO, AYACUCHO - Cavero Palomino, Yuri I. (2014)
The article discusses the results of the archaeological record made in a transverse segment Inka road and secondary character evidence remains of paved road and stairs. These evidences are located on both banks of the creek Tutiwayqo in district Tambillo Guamanga province, Ayacucho region. The road was part of a registered road cross was headed Huaychao, Inkapara and reached the Apurimac river valley; in the vicinity of Tambillo was articulated to the main road from the dairy farm Pukaray (current city of Ayacucho) was moving dairy Andahuaylas (Apurimac).